The Dynamic Damage Mechanisms and Failure Modes of Coal-Rock Masses under the Action of High Order P-Waves - Feng Li; Mingxin Bi; Jing Tian; Shuhao Fang (Shock and Vibration)
In the process of deep mining, the coal-rock masses were subjected to different types’ disturbance of dynamic loading, and they propagated to the depth of coal and rock in the forms of stress waves. It has been determined that coal-rock masses mainly show shear-compression failures under static pressure. However, under dynamic loading, they had consistently demonstrated crashing or splitting failure, which showed strong dynamic mechanical characteristics. Therefore, the propagation and interaction of stress waves have great effect for the dynamical damage of coal-rock masses. The current research regarding the dynamic mechanical characteristics of coal-rock masses is still in the qualitative analysis stage, with the dynamic damage mechanism and failure modes remaining unclear. Based on the propagation characteristics of a plane strain and cylindrical wave control equations, this paper obtained a cylindrical wave propagation frequency equation and established a dynamic calculation model for the radial, axial, and shear stresses under high order P-waves. We have noticed, most surprisingly, that the amplitude directions of the radial and axial stress waves were almost opposite, with the amplitude values being basically the same when the vibration remained stable. And the vibration amplitude of shear stress wave was found to be the largest. Therefore, the coal-rock masses generally experienced tensile and shear failures under high order P-waves. The following results can be obtained: tensile failure easily occurred to the surface or axis of cylindrical coal-rock masses when there was no confining pressure, and the coal-rock masses generally experienced tensile-shear failures when confining pressure was present. And we found that the vibration amplitudes and dimensionless radius (r/R) were in approximately the −0.5 power relationship, and the dimensionless wave numbers (kR), dimensionless frequency (wR), and the wave length of stress waves propagating in cylindrical coal-rock masses were mainly within 85, (0.1~1.8) × 105, and 0.24R~1.08R respectively.